Surat 1 Korintus dan Penerusannya dalam Gereja - Aloysius Purwo Hadiwardoyo (Jurnal Teologi (Journal of Theology), 2012)
Being left by Saint Paul for some months, there was seemingly a kind of disputes among the first Christians in Corinth about some moral and pastoral matters. As a positive response to such a situation, Saint Paul sent them a special letter. In that well-known letter, Saint Paul tried to expose his personal teaching about some aspects of Christian belief and Christian way of life.The teaching of Saint Paul, as far as it is formulated in his first letter to the Corinthians chapter 7, was concerned among other things about celibate life as well as about married life, about divorce, about mixed married, and about the widows. The apostle underlined the dignity of celibate life as well as the dignity of married life. He demanded all Christian couples to be faithful, one to each other. He recommended celibate life for the young Christian who were ready to live just only for the Kingdom of God.The Catholic Church has faithfully interpreted and implemented the teaching of Saint Paul, as well as the teaching of our Lord Jesus Christ, since the second century up to this century. Many catholic bishops, for example, have given the nihil obstat to the parish priest throughout the world, especially in Asia and Africa, to implement the so-called privilegium paulinum, even though they have also consistently taught that matrimony should be always indissoluble.